2020
DOI: 10.2147/jpr.s233617
|View full text |Cite
|
Sign up to set email alerts
|

<p>Regional Anesthesia for Pain Management After Orthopedic Procedures for Treatment of Lower Extremity Length Discrepancy</p>

Abstract: Introduction: The use of regional anesthesia techniques continues to expand in a wide variety of surgical procedures as the benefits and safety are increasingly appreciated. Limblengthening procedures are often associated with significant postoperative pain and high opioid requirements which may impact patient's recovery and increase risk of chronic pain and long-term opioid use. Methods: The current study retrospectively reviews our experience utilizing a novel peripheral nerve catheter (PNC) protocol for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Sample size was calculated using MedCalc Software version 16.8.4 (MedCalc Software bvba, Acacialaan 22, 8400 Ostend, Belgium). Based on minimum mean difference of 25% in morphine consumption [ 13 ] with α = 0.01 and β = 0.20, sample size for each group was estimated as 20. So, we include 30 patients in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size was calculated using MedCalc Software version 16.8.4 (MedCalc Software bvba, Acacialaan 22, 8400 Ostend, Belgium). Based on minimum mean difference of 25% in morphine consumption [ 13 ] with α = 0.01 and β = 0.20, sample size for each group was estimated as 20. So, we include 30 patients in each group.…”
Section: Methodsmentioning
confidence: 99%
“…O uso de BNPs em cirurgias ortopédicas de membros inferiores facilita a mobilização precoce (Kamel;Sethi, 2022). Em estudos como o de Arce Villalobos et al (2020), todos os pacientes começaram a fisioterapia e exercícios de sustentação de peso nas primeiras 24 horas pós-cirurgia. Pesquisas comparando BNPs com raquianestesia e anestesia geral mostram que os BNPs promovem mobilização mais rápida, melhor controle da dor e qualidade de sono.…”
Section: Deambulação Precoceunclassified
“…Complicações que causam danos permanentes variam de 0,015% a 0,09% (Mateen et al, 2021;Nobre et al, 2020;Danninger;Opperer;Memtsoudis, 2014). Arce Villalobos et al (2020) observaram uma maior recorrência de lesões nervosas em procedimentos com BNPs, destacando a necessidade de atenção redobrada a esse aspecto.…”
Section: Lesão Nervosaunclassified
“…In one pilot study, Alghamdi et al , with the use of acetaminophen, dexmedetomidine, dextromethorphan, and ketamine, were able to show effective pain management, parental satisfaction, and an absent need for perioperative opioid analgesia in children undergoing adenoidectomy [67]. Likewise, other studies have reported effective postoperative pain control achieved through peripheral nerve catheters with continuous infusion of local anesthetic agents, limiting the need for opioid use and the associated complications [68–71].…”
Section: Perioperative Implications Of Pediatric Obesitymentioning
confidence: 99%